Sequential treatment approaches in the management of BRAF wild-type advanced melanoma: a cost–effectiveness analysis. (17th October 2018) - Tarhini, Ahmad; Benedict, Agnes; McDermott, David; Rao, Sumati; Ambavane, Apoorva; Gupte-Singh, Komal; Sabater, Javier; Ritchings, Corey; Aponte-Ribero, Valerie; Regan, Meredith M; Atkins, Michael
Aim: To evaluate the cost–effectiveness of treatment sequences with checkpoint inhibitors in patients with BRAF wild-type melanoma.Materials & methods: Using a discrete event simulation model, cost and health outcomes were estimated. Pooled data from CheckMate 067/069 trials were used to calculate survival outcomes including treatment-free interval extrapolated over a patient's lifetime. Costs accounted for treatment, administration, toxicity, and disease management.Results: First-line anti-PD-1 + anti-CTLA-4 initiating sequences had the highest estimated mean survival gain (7.6–7.7 years), driven by a longer estimated mean treatment-free interval (5.3 years). Incremental costs per incremental quality-adjusted life year gained for anti-PD-1 + anti-CTLA-4 followed by chemotherapy were US$30, 955 versus anti-PD-1 initiating sequences, within the willingness-to-pay threshold.Conclusion: Anti-PD-1 + anti-CTLA-4 initiating sequences for BRAF wild-type melanoma are cost-effective versus anti-PD-1.